PERANCANGAN DIGITAL MARKETING BERBASIS ELECTRONIC BUSINESS PADA LATIF DISTRO KALIREJO LAMPUNG TENGAH - Latif Saifulloh, Ahmad (JMBI (Journal of Marketing and Business Intelligence), 2024)
Competition in the field of business increasingly sophisticated in line with the development of information technology at this time can create business opportunities for traders to make sales online. With the online technology of the merchants easily to conduct transactions without having to go to the desired place of sale. Internet facilities support the sellers to make sales online. But the facilities used to connect the Internet network on Latif Distro is not yet available, for it will be designed online sales program using photoshop, macromedia dreamweaver, php mysql and Xampp. Making this Application is done by observation and Interview method and then designed with System Development Life Cycle (SDLC) model. With the design of web-based sales is expected to help and attract customers and help increase sales in the Latif Distro. Facilitate consumers in shopping without having to come to the place of direct sales simply by online anytime and anywhere.